Spectroscopic analysis of the transverse excited C3Πu–B3Πg(0–0) UV laser band of N2 at room temperature: comments - Ranea Sandoval, Héctor F. (1979)
Recently Petit et al.published a paper devoted to a high-resolution spectroscopy study of the 0-0 laser band in the Second Positive System of molecular nitrogen and explaining the optical gain formation on its different branches.All the results by Petit et al. are equivalent to those previously published by Massone et al.and are in accordance with theoretical predictions reported by Tocho et al.Summarizing, we would comment as follows.